2012
DOI: 10.1111/j.1365-3156.2012.02962.x
|View full text |Cite
|
Sign up to set email alerts
|

Rural electrification in Brazil and implications for schistosomiasis transmission: a preliminary study in a rural community in Minas Gerais State, Brazil

Abstract: Abstractobjectives To evaluate the potential transmission of Schistosoma mansoni through well water pumped into households in a rural Brazilian community within the context of Brazil's rural electrification program Luz Para Todos (Light for All).methods All households were interviewed about their water facilities and domestic water use, all household members were examined for S. mansoni infections and positives treated, and malacological and water contact studies were performed between 2001 and 2009.results Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Greater house infestations of triatomine bugs, that spread Chagas disease, can occur from simple improvements in public streetlights, as documented in Yucatan, Mexico [ 46 ]. Electric pumps installed as part of a rural electrification project in Brazil were found to be a risk factor for schistosomiasis spread [ 47 ]. The urban mosquitos Aedes aegypti and Aedes albopictus that spread dengue fever, Zika, and chikungunya proliferate in man-made containers, such as tyres, pots and water storage containers [ 48 ].…”
Section: Main Textmentioning
confidence: 99%
“…Greater house infestations of triatomine bugs, that spread Chagas disease, can occur from simple improvements in public streetlights, as documented in Yucatan, Mexico [ 46 ]. Electric pumps installed as part of a rural electrification project in Brazil were found to be a risk factor for schistosomiasis spread [ 47 ]. The urban mosquitos Aedes aegypti and Aedes albopictus that spread dengue fever, Zika, and chikungunya proliferate in man-made containers, such as tyres, pots and water storage containers [ 48 ].…”
Section: Main Textmentioning
confidence: 99%
“…We considered all types of water in Box 1 as ‘safe’, and all types of sanitation in Box 1 as ‘adequate’. We considered ‘well’ to be a safe water source, except in Brazil, where ‘wells’ often consisted of pond-like water bodies, in contrast to the hand-dug wells in sub-Saharan Africa that are unlikely to contain snails or allow for water contact [36] . We considered use of soap during water contact as ‘good’ hygiene practice.…”
Section: Methodsmentioning
confidence: 99%
“…In terms of the effect of electrification on vector-borne disease, the results were also mixed. A cross-sectional study by Kloos, Quites, Oliveira, LoVerde, and Gazzinelli (2012) identified lower schistosomiasis infection rates among individuals in households with an electric well following a mass rural electrification programme in Brazil (Kloos et al, 2012). This could potentially be due to reduced use of streams and thus contact with contaminated water as a result of water getting pumped directly to the households (Kloos et al, 2012).…”
Section: Health Effects Of Electrificationmentioning
confidence: 99%
“…A cross-sectional study by Kloos, Quites, Oliveira, LoVerde, and Gazzinelli (2012) identified lower schistosomiasis infection rates among individuals in households with an electric well following a mass rural electrification programme in Brazil (Kloos et al, 2012). This could potentially be due to reduced use of streams and thus contact with contaminated water as a result of water getting pumped directly to the households (Kloos et al, 2012). In evaluating the effects of establishing an electricity supply to rural villages in Iran, however, a retrospective panel study by Izadi (2015) found that the presence of electricity in a village was not associated with the annual number of malaria cases (Izadi, 2015) and that village electrification may have in fact been harmful, with the availability of light after dark potentially leading to increased malaria transmission by encouraging people to spend more time outside after dark and attracting the mosquito vectors to light sources (Izadi, 2015).…”
Section: Health Effects Of Electrificationmentioning
confidence: 99%
See 1 more Smart Citation